The effect of using the balanced scorecard (BSC) on reducing banking services costs – An applied study on commercial banks in Palestine – - Al- Madhoun, Khaled Muhammad (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to measure the effect of the Balanced Scorecard (BSC), with its four dimensions (financial, clients, internal operations, learning and growth) on reducing banking services costs in commercial banks in Palestine. The study used the descriptive, analytical, and also the regression analysis methods. The study depends on the questionnaire which was addressed, to (general manager, financial director, observer, head of accounting department). The study sample contained (47) employees working in commercial banks in Palestine. The study results showed a significant effect of using the Balanced Scorecard (BSC) and its four dimensions (financial, clients, internal operations, learning and growth) on reducing banking services costs in commercial banks in Palestine, The study recommended the necessity for commercial banks departments in Palestine to pay more attention to clarifying the importance of the Balanced Scorecard (BSC) method, which is one of the modern methods of accounting and its role in reducing banking services costs. And developing service cost plans using the Balanced Scorecard (BSC) and paying attention to all dimensions of the Balanced Scorecard for its role in reducing the costs of the services provided.